Wewenang Sebagai Instrumen Penyelenggararaan Pemerintahan Dalam Sistem Negara Hukum - Qamar, Nurul; Rezah, Farah Syah (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2023)
A rule of law is a state that places the law, the principle of an independent and partial judiciary, as supreme command in the governance order, so that the executors of the functions of government positions do not have free will. By literature research, The urgency of authority as an instrument of government in the administration of a rule of law is that it must adhere to, develop, and practice the principle of a rule of law, which is based on the principle of legality, so that the legal authority of government originates from law. In a rule-of-law state, authority is used as an instrument for administering government, so that the basis for taking action is clear; therefore. So that authority as a legal instrument is measured by whether or not there is legal authority as governmental authority.